OECD employment outlook 2017 (Paris, 2017)
"The 2017 edition of the OECD Employment Outlook reviews recent labour market trends and short-term prospects in OECD countries. Chapter 1 presents a comparative scoreboard of labour market performance that encompasses the quantity and quality of employment, as well as the inclusiveness of the labour market. During the past decade, most countries managed to better integrate women and potentially disadvantaged groups into the labour market and improve the quality of the working environment, whereas earnings quality was more or less stable and labour market security worsened. Chapter 2 looks at the resilience of labour markets following the global crisis and shows how both structural reforms and expansionary fiscal policy mitigate the unemployment costs of adverse aggregate shocks. OECD countries generally have avoided an increase in structural unemployment, but not a marked deceleration of wage and productivity growth. Chapter 3 documents the impact of technological progress and globalisation on OECD labour markets over the past two decades. Technology is shown to have been strongly associated with both job polarisation and de-industrialisation. The impact of trade integration is difficult to detect and probably small, although rising imports from China has a small effect in depressing employment in manufacturing. Chapter 4 provides an exceptionally rich portrait of collective bargaining in OECD countries that makes it possible to understand better how national systems differ and the implications of those differences for economic performance."